2007
DOI: 10.1002/cyto.a.20374
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐automated imaging system to quantitate Her‐2/neu membrane receptor immunoreactivity in human breast cancer

Abstract: Background: Immunocytochemical methods for quantitating Her-2/neu immunoreactivity rest on subjective semi-quantitative interpretations with resulting interobserver, intraobserver, and fatigue variability. Methods: To standardize and quantitate measurements of Her-2/neu immunoreactivity, we created epithelial-recognition and specific membrane-recognition algorithms, which could image breast cancer cells against a background of stroma, compartmentalize the cancer cell into nucleus, cytoplasm and membrane, and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 12 publications
3
33
0
Order By: Relevance
“…[34][35][36] Rizzardi et al 37 also reported a good performance of computerassisted image classification and immunohistochemistry quantification in ovarian serous carci- noma. Our algorithms performed well in the highly varied histologic types of ovarian carcinoma, with a relatively low level of manual correction needed (B8%, data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…[34][35][36] Rizzardi et al 37 also reported a good performance of computerassisted image classification and immunohistochemistry quantification in ovarian serous carci- noma. Our algorithms performed well in the highly varied histologic types of ovarian carcinoma, with a relatively low level of manual correction needed (B8%, data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…In the literature, there are several publications on automatic detection and classification of nuclei and FISH analysis on fluorescent images (35)(36)(37) and complex automated segmentation methods for membrane and muscle fiber for example (31,38).…”
Section: Quantitative Imagingmentioning
confidence: 99%
“…Brightfield virtual microscopy or whole slide imaging (WSI)-the naming convention is not consistent yet-became commercially available and starts to be established in pathology (28)(29)(30)(31)(32). WSI means that complete sections, cytospins, and smears can be digitized automatically in high-enough resolution that is appropriate for diagnosis.…”
mentioning
confidence: 99%
“…The analysis of immunohistochemical staining patterns usually measures speciWc single targets rather than the relatively complex and intricate disease patterns, for example those seen on haematoxylin and eosin staining, therefore immunohistochemical studies are inherently amenable to automated image analysis (Joshi et al 2007). Sources of variability in immunohistochemistry are numerous and include Wxation conditions, specimen pre-treatment, reagents, detection methods, and interpretation of results.…”
Section: Introductionmentioning
confidence: 99%